1971
DOI: 10.1017/s0021859600064522
|View full text |Cite
|
Sign up to set email alerts
|

Plant population, shading and thinning studies in wheat

Abstract: Three wheat experiments are described in which a range of plant populations were shaded during different periods of development; in two of the experiments plant thinning was also carried out at a number of growth stages. Shading during the period of ear development caused an appreciable decrease in grain yield by decreasing the number of grains per ear. Shading during the grain filling period also reduced grain yield, this being brought about by decreased grain size. Thus in contrast to the barley experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
3
1

Year Published

1975
1975
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 8 publications
(5 reference statements)
4
50
3
1
Order By: Relevance
“…On the other hand, the lower number of tillers for variety Digelumight be attributed to the death of tillers due to low rainfall late in the growing season. This result was in agreement with Willey and Holliday (1971) where they indicated that high seeding rates generally increased number of spikes per square meter, although fewer and smaller kernels per spike can occur which results in little change in total grain yield. Kumar et al (1991) and Ahmad et al (1999) also confirmed the present result, where higher sowing rates increased the number of tillers mG 2 due to more plant population but number of tillers per seedling decreased with increased in seed rate.…”
Section: Plant Height (Cm)supporting
confidence: 90%
“…On the other hand, the lower number of tillers for variety Digelumight be attributed to the death of tillers due to low rainfall late in the growing season. This result was in agreement with Willey and Holliday (1971) where they indicated that high seeding rates generally increased number of spikes per square meter, although fewer and smaller kernels per spike can occur which results in little change in total grain yield. Kumar et al (1991) and Ahmad et al (1999) also confirmed the present result, where higher sowing rates increased the number of tillers mG 2 due to more plant population but number of tillers per seedling decreased with increased in seed rate.…”
Section: Plant Height (Cm)supporting
confidence: 90%
“…wheat (Slafer & Rawson, 1994) and barley (Willey & Holliday, 1971). Moreover, the experimental decrease of competition for assimilates by removing tillers from the plant in spring wheat resulted in lower floret abortion (Mohamed & Marshall, 1979).…”
Section: Interrelationships Between the Characters Studiedmentioning
confidence: 99%
“…The number of grains of the second tillers (T 2) was not significantly affected, although it increased by 13.3%. In field experiments, several authors (Puckridge & Donald, 1967;Willey & Holliday, 1971;Fischer, Aquilar, Mauver & Rivas, 1976) have reported that an increase in grain yield was positively correlated with an increase in grain number. Our results indicated that grain yield per ear was strongly associated with grain number per ear.…”
Section: Grain Number Per Earmentioning
confidence: 99%
“…Kernel mass depends on the availability of plant assimilates during the stage of grain-filling, and this is closely related to the leaf area duration after anthesis (Spiertz, Ten Hag & Kupers, 1971;Thome, 1974;Annandale, Hammes & Nel, 1987). Puckridge and Donald (1967) and Willey and Holliday (1971) found that very high numbers of grains can only be achieved in dense crops, in which radiant energy for grain-filling will be limited and grain weight will decrease due to less reserve carbohydrate in ear-bearing shoots after anthesis. Briggs (1991) concluded that genotypic variation in kernel mass (or seed size) within wheat cultivars is common and will depend on the levels of environmental stress in a particular growing season, as well as on the specific plasticity of individual cultivars.…”
Section: Kernel Mass Tmentioning
confidence: 99%